Caudal agenesis with closed spinal dysraphism, a case report - Lacunza Paredes, Rommel Omar (2020)
Caudal agenesis is a rare pathology, its diagnosis and fetal evaluation are complex. The presence of closed spinal dysraphism at the level of the sacrum should compel us to evaluate the anatomy of the sacrum. The evaluation of the medullary cone is very useful to evaluate and exclude closed spinal dysraphism and caudal agenesis. We report a rare case of caudal agenesis